2016
DOI: 10.1080/17441692.2016.1170183
|View full text |Cite
|
Sign up to set email alerts
|

Deportation and mental health among migrants who inject drugs along the US–Mexico border

Abstract: Objective This study describes the prevalence and factors of depressive symptoms among a sample of persons who inject drugs (PWID) with a history of deportation from the US in Tijuana, Mexico. In 2014, 132 deported PWID completed a structured questionnaire. Depressive symptoms were measured using the Center for Epidemiologic Studies Short Depression Scale (CESD-10) screening instrument. Eligible participants were ≥18 years old, injected drugs in the past month, spoke English or Spanish, and resided in Tijuana.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 57 publications
0
8
0
3
Order By: Relevance
“…To date, no study has examined if detentions and deportations are influencing the alcohol and drug using behaviors of US-citizen Latinos. Studies that have investigated the relationship between substance use and deportation have exclusively focused on deported migrants in post-deportation settings (e.g., in Mexico and Latin America) (Horyniak, Pinedo, Burgos, & Ojeda, 2017;Ojeda et al, 2011;Pinedo, Burgos, Robertson, et al, 2014;Pinedo et al, 2018). Due to the emotional and psychological consequences of detentions and deportations, we can broadly speculate that US-citizen Latinos who have been impacted by the detention or deportation of others in their social networks (e.g., family, friends) may be more susceptible to use alcohol and drugs as a coping mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no study has examined if detentions and deportations are influencing the alcohol and drug using behaviors of US-citizen Latinos. Studies that have investigated the relationship between substance use and deportation have exclusively focused on deported migrants in post-deportation settings (e.g., in Mexico and Latin America) (Horyniak, Pinedo, Burgos, & Ojeda, 2017;Ojeda et al, 2011;Pinedo, Burgos, Robertson, et al, 2014;Pinedo et al, 2018). Due to the emotional and psychological consequences of detentions and deportations, we can broadly speculate that US-citizen Latinos who have been impacted by the detention or deportation of others in their social networks (e.g., family, friends) may be more susceptible to use alcohol and drugs as a coping mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…For families seeking to reunite with the deportee in Mexico, ensuring that children have access to social (e.g., education) and other institutions (e.g., health care) is critical to promoting their well-being. It is critical that all parents and children have legal identification in the receiving country (e.g., Mexico), in order to prevent an undocumented status, which would prevent accessing public services (e.g., health care) and the labor market (e.g., employment opportunities) (61,73).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the framework proposes that the deportation process and event also affect the deportee's outcomes and the post-deportation circumstances of the deportee may have a reciprocal effect on the family and household remaining in the U.S. The well-being of migrants post-deportation has been examined in some diverse contexts (9,18,(57)(58)(59)(60)(61) though the longitudinal and reciprocal relationships with their U.S.-based families have not received attention. This framework should be tested in qualitative and quantitative studies with diverse national origin migrant communities to better understand the impacts of deportation and family separation.…”
Section: Conceptual Model: a Framework For Understanding The Outcomesmentioning
confidence: 99%
“…A growing body of evidence has found that deportation has significant detrimental impacts on health. In particular, deported migrants report poor psychological wellbeing and high rates of mental health disorders (Bojorquez, Aguilera, Ramirez, Cerecero, & Mejia, 2015; Brotherton & Barrios, 2009; Pinedo et al, 2016; Wheatley, 2011), harmful patterns of substance use (Horyniak, Pinedo, Burgos, & Ojeda, 2016; Zhang et al, 2015), engagement in behavioural risk practices which place them at risk of acquiring HIV or sexually transmitted infections (Martinez-Donate et al, 2015; Pinedo, Burgos, & Ojeda, 2014) and often face significant barriers to accessing healthcare (Fernández-Niño, Ramírez-Valdés, Cerecero-Garcia, & Bojorquez-Chapela, 2014; Rosales Martinez, Bojorquez Chapela, Leyva Flores, & Infante Xibille, 2017).…”
Section: Introductionmentioning
confidence: 99%